Parental Vigilance and the Discursive Construction of Local School Policy (Alberta Journal of Educational Research, 2004)
This article examines how a small group of high-socioeconomic status (high-SES) parents organized community opposition to the integration of a special-needs student into a grade 3 classroom in an urban elementary school in Ontario. Using data gathered in a participant observation study, this article shows hoiv parents came to believe that existing special education policy placed the individual needs of the special education student over the needs of the collective. It explicates parents' subsequent efforts to enter into a social discursive process to challenge the policy and ultimately co-construct unofficial integration guidelines specific to the local school. In forcing the school board to explicate special education policy and practice, the parents underscored the nature of schools as contested sites of policy negotiation and established themselves as players in the policy development arena. Furthermore, this article highlights the importance of both history and local context in policy development and implementation and suggests that special education initiatives are best conceptualized as nested in local communities. The article concludes with a suggestion for future research on special education policy and community responses to integration.